HYDROLIZE CANE WASTE To GLUCOSE by Trichoderma viride (Study on Cane Waste Concentration and Fermentation Time) - Saparianti, Ella; Dewanti, T.; Dhoni, S. K. (Jurnal Teknologi Pertanian, 2004)
Trichoderma viride is the one of selulolitic microorganisms that can produce glucose  from selulose rich material such as cane waste.  This research was conducted to study the effect of cane waste concentration and  fermentation time on glucose yield of the liquid.  Completely Randomized Block Design (CRBD) was employed on this research with two factors.  Factor I is cane waste concentration (2, 5, 8%) and factor two is fermentation time (5, 10 15 days). The result showed that cane waste concentration significantly (α=0,01) affected  glucose yield, selulolitic activity, viscosity, and total dissolved  solid.   Fermentation time siginificantly (α=0,01)  affected glucose yield, total molds, selulolitic activity, viscosity, and total dissolved  solid. The high glucose yield (13,442%)  was reached at  cane waste concentration of 8% and  fermentation time of 15 days.   This treatment caused selulose of 18,829% was hydrolyzed with selulolitic activity of  74,678 NCU, total molds of 65,33 x 105, viscosity of 9,387 x 10-3 centipoise , and total dissolved  solid of 6,47 (brix).   Key words : cane waste, glucose, selulolitic activity, Trichoderma viride